How Neutrophils Shape Adaptive Immune Responses - Leliefeld, Pieter H. C.; Koenderman, Leo; Pillay, Janesh (Frontiers in Immunology, 2015)
Neutrophils are classically considered as cells pivotal for the first line of defence against invading pathogens. In recent years, evidence has accumulated that they are also important in the orchestration of adaptive immunity. Neutrophils rapidly migrate in high numbers to sites of inflammation (e.g. infection, tissue damage, cancer) and are subsequently able to migrate to draining lymph nodes. Both at the site of inflammation as well as in the lymph nodes neutrophils can engage with lymphocytes and antigen-presenting cells. This crosstalk occurs either directly via cell-cell contact or via mediators such as proteases, cytokines and radical oxygen species. In this review we will discuss the current knowledge regarding locations and mechanisms of interaction between neutrophils and lymphocytes in the context of homeostasis and various pathological conditions. In addition we will highlight the complexity of the microenvironment that is involved in the generation of suppressive or stimulatory neutrophil phenotypes.